2017
DOI: 10.1111/nicc.12315
|View full text |Cite
|
Sign up to set email alerts
|

Repeated sleep‐quality assessment and use of sleep‐promoting interventions in ICU

Abstract: To describe sleep quality using repeated subjective assessment and the ongoing use of sleep-promoting interventions in intensive care. It is well known that the critically ill experience sleep disruption while receiving treatment in the intensive care unit. Both the measurement and promotion of sleep is challenging in the complex environment of intensive care unit. Repeated subjective assessment of patients' sleep in the intensive care unit and use of sleep-promoting interventions has not been widely reported.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
18
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 33 publications
(49 reference statements)
4
18
0
9
Order By: Relevance
“…Simons et al investigated the relationship between noise in intensive care and sleep quality and reported a 24‐hour noise level of 54.0 dBA (± 2.4) and a mean RCSQ score of 56 ± 24, concluding that noise levels are significantly correlated with sleep quality 41 . Menear et al and Carrera‐Hernández et al examined sleep quality and associated factors in patients in intensive care and reported mean RCSQ values of 47.9 ± 24.1 and 52.92, respectively, both emphasizing that sleep quality is particularly affected by noise 42,43 . Studies 44,45 have also emphasized that noise experienced in the ICU produces direct adverse physiological and psychological effects and can result in indirect negative health outcomes deriving from decreased sleep quality and duration, difficulty in falling asleep, and excessive noise levels, which have been reported in ICUs 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Simons et al investigated the relationship between noise in intensive care and sleep quality and reported a 24‐hour noise level of 54.0 dBA (± 2.4) and a mean RCSQ score of 56 ± 24, concluding that noise levels are significantly correlated with sleep quality 41 . Menear et al and Carrera‐Hernández et al examined sleep quality and associated factors in patients in intensive care and reported mean RCSQ values of 47.9 ± 24.1 and 52.92, respectively, both emphasizing that sleep quality is particularly affected by noise 42,43 . Studies 44,45 have also emphasized that noise experienced in the ICU produces direct adverse physiological and psychological effects and can result in indirect negative health outcomes deriving from decreased sleep quality and duration, difficulty in falling asleep, and excessive noise levels, which have been reported in ICUs 46 .…”
Section: Discussionmentioning
confidence: 99%
“…The RCSQ was able to be completed in 100% of attempts, a completion rate higher than other studies, [28][29][30] that demonstrates its feasibility when administered as a repeated assessment in an ICU cohort. Overall, sleep was classified as fair with a mean RCSQ of 52±25, which is comparable to previously reported ICU means of 34-60.…”
Section: Resultsmentioning
confidence: 78%
“…Overall, sleep was classified as fair with a mean RCSQ of 52±25, which is comparable to previously reported ICU means of 34-60. [28][29][30] The even distribution of RCSQ scores across poor, fair and good sleep groups suggests that all correlation efforts were conducted across the entire spectrum of patient-perceived sleep quality.…”
Section: Resultsmentioning
confidence: 99%
“…Sixth, previous studies suggested that long naps affect nighttime sleep patterns [ 35 , 36 ] and the quality of sleep [ 37 ]. Not only the total sleeping time but also the quality of the sleep is important [ 38 , 39 , 40 , 41 , 42 ]. However, we did not collect information relevant to childhood development, sleep quality and individual family patterns of sleep behavior, which are significant factors for the sleep of children and the issue of poor parenting.…”
Section: Discussionmentioning
confidence: 99%